Monoamniotic twin pregnancy: continuous inpatient electronic fetal monitoring—an impossible goal? - Quinn, Kristen H.; Cao, Carol Tran; Lacoursiere, D. Yvette; Schrimmer, David (American journal of obstetrics and gynecology, 2011)
We sought to determine the effectiveness of continuous fetal monitoring in monoamniotic twins and assess the percentage of successful monitoring across gestation. This was a single-center retrospective cohort analysis of monoamniotic twins. Each subject's entire electronic fetal heart tracing was reviewed. The primary outcome measure was the percentage of time that 0, 1, and 2 fetuses were successfully monitored. To compare the effectiveness of monitoring across gestation, these data were stratified by gestational age (<27, 27-30, and >30 weeks). A total of 10,402 hours of fetal monitoring were reviewed for 17 monoamniotic twin pairs. Successful monitoring of 0, 1, and 2 fetuses occurred 21.2%, 27.1%, and 51.6% of the time, respectively. Successful monitoring of both fetuses was positively correlated with gestational age (<27 weeks 37%; 27-30 weeks 51%; >30 weeks 57%; P < .007). Successful monitoring of both fetuses occurred 51.6% of the time. Continuous monitoring efficiency improved with advancing gestational age.